2001
DOI: 10.4049/jimmunol.167.9.5316
|View full text |Cite
|
Sign up to set email alerts
|

IL-1 Plays a Critical Role in Oral, But Not Dermal, Wound Healing

Abstract: Wound healing is a well-orchestrated complex process leading to the repair of injured tissues. After injury, proinflammatory cytokines act as important modulators of the inflammatory process. IL-1 expression has been regarded as necessary for healing; however, its effects have also been implicated in delayed wound repair. Currently, there is no consensus or direct evidence that IL-1 activity plays a central role in the healing process. The present investigation was undertaken to define the role of IL-1R signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
71
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 22 publications
(12 reference statements)
6
71
1
1
Order By: Relevance
“…These factors have the ability to stimulate the release of other cytokines, the promotion of angiogenesis, and production of extra-cellular matrix in the wound healing process after surgery. IL-1 and TNFα have been shown to be essential in the early phases of wound healing (14,(25)(26)(27). In this study, we found increased levels of both IL-1 and TNFα on postoperative day 1, in the early phase of wound healing.…”
Section: Discussionsupporting
confidence: 60%
“…These factors have the ability to stimulate the release of other cytokines, the promotion of angiogenesis, and production of extra-cellular matrix in the wound healing process after surgery. IL-1 and TNFα have been shown to be essential in the early phases of wound healing (14,(25)(26)(27). In this study, we found increased levels of both IL-1 and TNFα on postoperative day 1, in the early phase of wound healing.…”
Section: Discussionsupporting
confidence: 60%
“…Nathan (9) showed that TNF was involved in the late phase of wound healing, in switching from the tissue-damaging mode to the tissue repair-promoting mode after debris and dead cells were no longer present. Another explanation is that IL-1 might play an essential role in antibacterial defense in a challenging environment in which microflora are deleterious to the wound-healing process (17). As a result, the early improvement of periodontal healing has been lost in animals treated long-term with IL-1 and TNF soluble receptors compared with the untreated animals.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1 can induce apoptosis (14) or antagonize apoptosis through activation of NF-B depending on the cell type (15). A small amount of IL-1 is necessary for host defense and wound healing (16), particularly in a challenging environment (17), whereas overproduction of IL-1 can hinder the early phase of wound healing (18,19). Two primary IL-1Rs (IL-1RI and IL-1RII) have been identified.…”
Section: Short-and Long-term Effects Of Il-1 and Tnf Antagonists Onmentioning
confidence: 99%
“…IL-1 knockout mice demonstrated poor healing of oral wound compared to controls, but dermal wound healing is unaffected. 27 Similarly, increased IL-1 concentration has been associated with poor healing of skin in mice. 28 Thus, elevated levels of IL-1 seem to be detrimental to healing, so blockade of IL-1 may be advantageous postoperatively.…”
Section: Discussionmentioning
confidence: 99%